Output power boosting of a photovoltaic panel based on various back pipe structures: a computational study. Issue 1 (August 2021) - Bayoumi, A; Abdo, G M; Emara, A A
Abstract: The efficiency of photovoltaic panels (PV) drops due to the rise in temperature, which leads to a decrease in the PV output power. A PV/Thermal system is therefore used as a solution to increase the output power from the PV panels. Comsol Multiphysics software program, a simulator-based Finite Element Method (FEM) tool, and Matlab program simulations are used to perform this electro-thermal model. The simulation process for different back pipes follows a serpentine, and a new shape of pipes called (square shapes) which are attached under the PV module. These shapes were specifically chosen for higher conversion efficiency and increase the heat transfer of the system. Additionally, a comparison between electrical parameters and heat transfer characteristics of water and CuO/water nanofluid in a PV cooling system has been studied. The new shape leads to improve the photovoltaic (PV) module parameters, such as short circuit current ISC, open-circuit voltage VOC, and maximum power Pmax for a new shape more than the serpentine shape. These parameters are calculated under Air Mass 1.5 G (AM1.5G) with 1000 W/m2 of irradiance which is considered the average irradiance at the MENA (The Middle East and North Africa) region throughout the year. The results exhibit the PV module's total enhancement by using the new shape with CuO nano-fluid about 24.7 %.